Google this. - McFedries, P. (IEEE spectrum)
This paper discusses how the the word Google referring to the search engine, has been turned into a verb, and how certain activities are now referred to using this verb. The article also discusses the word modders, a cross between hot rodders and modify, referring to people who modify their computers.